2013
DOI: 10.1097/mpa.0b013e31827305b8
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Pancreatic Duct Caliber to Width of Pancreatic Gland by Endosonography Is Predictive of Pancreatic Cancer

Abstract: A PDG ratio is a good predictor of PC and is better than PD dilation. This sign should be routinely used by endosonographers to improve EUS diagnostic capability of PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
3
12
0
2
Order By: Relevance
“…However, in pancreatic carcinoma patients, the ratio was increased to more than 0.5. This was confirmed by Eloubeidi et al [23]. Positive predictive value, negative predictive value, sensitivity, specificity, and accuracy of PDG greater than or equal to 0.34 for detecting cancer were 87, 99, 94, 97, and 97%, respectively.…”
Section: Characterization Of Pancreatic Massessupporting
confidence: 71%
“…However, in pancreatic carcinoma patients, the ratio was increased to more than 0.5. This was confirmed by Eloubeidi et al [23]. Positive predictive value, negative predictive value, sensitivity, specificity, and accuracy of PDG greater than or equal to 0.34 for detecting cancer were 87, 99, 94, 97, and 97%, respectively.…”
Section: Characterization Of Pancreatic Massessupporting
confidence: 71%
“…La topographie du cancer était majoritairement l'uncus et la tête du pancréas dans 61,2% (n=11), caudale dans 16,6% (n=3), isthmique et corporéale dans 11,1% (n=2), ce qui concorde bien avec les données de la littérature (26) (27).…”
Section: Discussionunclassified
“…L'excellente résolution en contraste de ces séquences permet de détecter les tumeurs de petite taille <2cm ne déformant pas les contours du pancréas, et les lésions isodenses difficilement repérables en TDM (29)(30)(31). L'IRM est également supérieure au scanner dans la détection (intérêt des séquences de diffusion) et surtout la caractérisation des métastases hépatiques, et elle est dans ce cadre recommandée en cas de tumeur présumée résécable à l'issue du bilan TDM s'il existe un doute sur la nature d'une ou plusieurs lésions hépatiques (27) En conclusion Même si le risque de survenue de cancer sur PCC reste faible, certains éléments sémiologiques permettent d'aider au diagnostic. La présence d'une masse tissulaire chez un patient porteur d'une PCC doit faire évoquer le diagnostic de cancer en première intention ce d'autant qu'il existe une dilatation de la voie biliaire principale et des calcifications pancréatiques peu nombreuses.…”
Section: Discussionunclassified
“…A study from 1999 11 showed that the sensitivity of EUS-FNA for small lesions was modest while another study showed that diagnostic accuracy rises as the size of the mass increases with a reduction in accuracy for lesions more than 40 mm 12 . While additional endoscopic ultrasound imaging features may aid in the differentiation between solid pancreatic mass lesions 13 and are helpful for predicting the possibility of adenocarcinoma 14 , tissue diagnosis is essential for further clinical management.…”
Section: Introductionmentioning
confidence: 99%